THE INFLUENCE OF WORK DISCIPLINE, WORK ENVIRONMENT AND WORK CULTURE ON JOB SATISFACTION OF GAMPONG APPARATUS IN THE DISTRICT AREA MUARA ONE LHOKSEUMAWE CITY - Sukma Abdillah; Hamdiah; Nur Faliza; Aiyub (RADJA PUBLIKA, 2024)
Muara Satu is a sub-district located in the city of Lhokseumawe, consisting of 11 villages. This study aims to examine the relationship between work discipline, work environment, and work culture on the job satisfaction of employees. Using a quantitative approach with saturated sampling, 66 respondents were obtained as the research sample. The data analysis methods used in this study are multiple linear regression analysis, instrument testing, classical assumption testing, hypothesis testing, and determination coefficient testing with the help of SPSS 22 software program. The results of the partial tests indicate that work discipline, work environment, and work culture have a significant effect on job satisfaction. This is proven by an F-value greater than the F-table value (13.720 > 2.75) and a significance level of F-value at 0.000 < 0.05. Work discipline has a positive effect on job satisfaction, as evidenced by a t-value greater than the t-table value (2.389 > 1.669) with a significance level of 0.000 < 0.05. The work environment also has a positive effect on job satisfaction, as evidenced by a t-value greater than the t-table value (2.224 > 1.669) with a significance level of 0.000 < 0.05. Work culture positively influences job satisfaction, as evidenced by a t-value greater than the t-table value (2.365 > 1.669) with a significance level of 0.000 < 0.05.